Cognitive change in rehabilitation patients with dementia: prevalence and association with rehabilitation success - Dutzi, Ilona; Schwenk, Michael; Kirchner, Marietta; Bauer, Jürgen M.; Hauer, Klaus (Journal of Alzheimer's disease, 2017)
Background: Dementia is a frequent diagnosis in geriatric rehabilitation. Studies in patients with dementia on the development of their cognitive status during rehabilitation and its relation to functional outcomes have been scarce. Objectives: To de
Gesehen am 07.11.2018